PELATIHAN PENERAPAN MODEL TES KEBUGARAN PELAJAR NUSANTARA (TKPN) PADA GURU OLAHRAGA DI KOTA JAYAPURA - Sutoro, Sutoro; Womsiwor, Daniel; Yudistira, Indra; Putra, Miftah Fariz Prima (Jurnal Abdi Insani, 2024)
Fitness dimension is a very important aspect in Sports Education. That is why, sports teachers try to improve students' fitness levels in the sports learning process at school. Some examples of fitness tests that have developed in the Education environment are the Nusantara Student Fitness Test (TKPN) which is useful for measuring a person's physical fitness in carrying out daily activities without experiencing excessive fatigue. TKPN has five test items, namely BMI (Body Mass Index), Measuring Height and Weight, V Sit and Reach, Sit-Up (Lying Down), Squat Thrust, Pacer test. The purpose of this activity is to provide comprehensive training and assistance related to the implementation of TKPN for Sports teachers in Jayapura City, Papua. Community service activities are carried out through four stages, namely pretest, training, assistance, and posttest. The results of community service activities show that there has been an increase in knowledge related to TPKN among community service participants. Participants are very happy with the training because TKPN can be an alternative in conducting fitness tests on students. Community service participants can apply TKPN correctly. The results of the TKPN participants' community service for their students show that the fitness level of students in Jayapura city is still in the category of less. The results of this poor fitness level are the main task of sports teachers so that students in the future have a very good level of fitness.